Multifunctional Coating Improves Cell Adhesion on Titanium by using Cooperatively Acting Peptides. Issue 15 (3rd March 2016) - Pagel, Mareen; Hassert, Rayk; John, Torsten; Braun, Klaus; Wießler, Manfred; Abel, Bernd; Beck‐Sickinger, Annette G.
Abstract: Promotion of cell adhesion on biomaterials is crucial for the long‐term success of a titanium implant. Herein a novel concept is highlighted combining very stable and affine titanium surface adhesive properties with specific cell binding moieties in one molecule. A peptide containingl ‐3, 4‐dihydroxyphenylalanine was synthesized and affinity to titanium was investigated. Modification with a cyclic RGD peptide and a heparin binding peptide (HBP) was realized by an efficient on‐resin combination of Diels–Alder reaction with inverse electron demand and Cu I catalyzed azide–alkyne cycloaddition. The peptide was fluorescently labeled by thiol Michael addition. Conjugating the cyclic RGD and HBP in one peptide gave improved spreading, proliferation, viability, and the formation of well‐developed actin cytoskeleton and focal contacts of osteoblast‐like cells. Abstract : Let′s stick together : An efficient on‐resin combination of a Diels–Alder reaction with inverse electron demand and a Cu I catalyzed azide–alkyne cycloaddition is used to link a stable and affine TiO2 ‐binding peptide to two cell adhesive motifs. The multifunctional construct improved the cell adhesion of osteoblast‐like cells through the cooperative action of the peptides. DOPA=l ‐3, 4‐dihydroxylphenylalanine.